CO2 methanation : effective Ni-based catalysts and mechanisms over Ru/Al2O3 - Yong, Yan (2017)
The hydrogenation of CO2 at atmospheric pressure casts a direction for researchers to recycle the atmospheric carbon and subsequently reduce the greenhouse gas effect. Several efforts have been devoted to the development of an effective and stable catalyst for this reaction. Ni supported on Y2O3 catalysts were obtained from two different Y sources, Y2O3 that calcined from Y4O(OH)9(NO3) and Y4O(OH)9(NO3) directly. Compared to the ones from Y2O3 (denoted as Ni-Y2O3), the catalysts prepared from Y4O(OH)9(NO3) (denoted as Ni/Y2O3) showed superior activity for CO2 methanation, which was attributed to the enrichment of surface medium basic sites that of great importance for CO2 activations. However, with high metal loadings such as 20%, strong basic sites appeared which resulted in a high sensitivity to coke formation. Moreover, the reaction mechanism for CO2 methanation over Ni supported on Y2O3 has been proposed involving carbonates and formates species as key intermediates. The higher reactivity towards H2 for formates over Ni/Y2O3 than that over Ni-Y2O3 was found, which probably was the rate-determining step for CH4 formations. Temperature-programmed reduction by H2 (H2-TPR) further revealed that a stronger interaction between Ni species and the support for the reference Ni-Y2O3, if compared to that of Ni/Y2O3. A W doped Ni-Mg mixed oxide catalyst (NiWMgOx) was prepared by homogeneous precipitation and employed for the methanation of CO2. The addition of W remarkably promoted the methanation activity if compared to the undoped NiMgOx catalyst with improved stability and anti-CO-poison ability. Characterization techniques including in situ diffuse reflectance infrared Fourier Transform spectroscopy (DRIFTS), temperature-programmed desorption of CO2 (CO2-TPD) and H2-TPR were applied for both NiMgOx and NiWMgOx. The superior reactivity of monodentate formate towards H2 than that of bidentate formate species was identified and doping with W favored the formation of the former during the methanation of CO2, which well agreed with the activity results. W addition also increased the formation and the stability of surface basicity sites, along with an enhancement of the Ni-Mg interaction in favor of anchoring the Ni sites, all of which were responsible for the enhanced CO2 methanation activity and the improved stability. Mechanistic studies of CO2 methanation have been carried out on Ru/Al2O3. The structural configuration of Ru species over Ru/Al2O3 catalysts at different Ru loadings has been characterized by infrared reflection absorption spectroscopy (IRAS) for CO adsorption. Supported Ru monolayers, in which metal atoms directly interacted with the support, were plentiful over 1% Ru/Al2O3, exhibiting a high CO yield for the hydrogenation of CO2 at ambient pressure. An increasing preference for methanation was observed on Ru/Al2O3 with higher Ru loadings, over which a tendency for the exclusive formation of three-dimensional (3D) nanoclusters of multilayers appeared. Density functional theory (DFT) calculations over Ru9/Al2O3, as the representative model of supported Ru monolayers, and Ru35/Al2O3, as the representative model of supported 3D nanoclusters, demonstrated that the energy barrier of reversed water gas shift (RWGS) was lower than that of the methanation on Ru monolayers while CH4 production was energetically favored on top sites of 3D Ru nanoclusters. Moreover, the incorporation of the peripheral O into the final products of CO2 hydrogenation was predicted as a critical step during the RWGS at the metal-support interfaces, which was validated by isotope exchange mass spectrometry (MS) experiments.